EFFICACY AND SAFETY OF USING COLISTIN IN NEONATES : A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Colistin is a cationic polypeptide antibiotic that belongs to the family of polymyxins and kills bacteria by interfering with the functioning of the bacterial cell. When given intravenously, colistin has the potential to cause a number of potentially harmful side effects, the most prevalent of which is nephrotoxicity. Recent studies have shown that patients who receive therapy with intravenous colistin run a risk of developing decreased kidney function ranging from 7.5% to 18.6% of the time. This risk is higher in patients who are older. However, it is essential to keep in mind that treatment with intravenous colistin, in the same way as treatment with other nephrotoxic drugs can result in conditions such as infection, septic shock, and the failure of several organs, it is vital to keep in mind that treatment with intravenous colistin. The bactericidal actions of colistin are demonstrated to be effective against a significant proportion of Gram-negative aerobic bacilli. It wasn't until the 1950s that it was first used in the United States, but by the 1980s, intravenous versions of the drug had been phased out due to the nephrotoxicity they caused. However, due to a rise in the incidence of illnesses caused by carbapenem-resistant Gram-negative (CRGN) bacteria and a dearth of newly developed antimicrobial drugs that are active against multidrug-resistant Gram-negative germs, the effectiveness of colistin has been called into question once again. The effectiveness of colistin in newborns might range anywhere from 50 to 98 percent. In this particular research endeavor, hyponatremia was identified as a potential adverse impact.